ANALYSIS OF ACCOUNTABILITY AND TRANSPARENCY OF VILLAGE FUND ALLOCATION MANAGEMENT IN PEMATANG GAJAH VILLAGE, JAMBI LUAR KOTA DISTRICT, MUARO JAMBI REGENCY - Widiyati, Sri; Yudi, Yudi; Rahayu, Rahayu (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study analyzes the accountability and transparency of village fund allocation management. This study was conducted in Pematang Gajah Village, Jambi Luar Kota District, Muaro Jambi Regency. This study uses a quantitative research type with a descriptive approach. The type of data used is primary data. The respondents in this study numbered 20 people. The data collection technique used was a survey technique, which involved distributing questionnaires. The results of this study indicate that the accountability and transparency of village fund allocation management in Pematang Gajah Village, Jambi Luar Kota District, Muaro Jambi Regency on the accountability program indicators obtained the highest percentage and has been running well. Processes of accountability, transparency, honesty, law accountability, and policy accountability have been running well and have followed applicable regulations. Keywords: Accountability; Transparency; Village Fund Allocation